Epstein-Barr Virus-Negative Associated with Sinonasal Lymphoepithelial Carcinoma –A Rare Case Report - Salleh, Mohamad Najib; Hasny, Nurul Syuhadah; Ramli, Ramiza Ramza; Mohamad, Sakinah; Md Shukri, Norasnieda; Azman, Nusaibah; Hussain, Faezahtul Arbaeyah (International Journal of Human and Health Sciences (IJHHS), 2023)
Lymphoepithelial carcinoma (LEC), also known as lymphoepithelioma-like carcinoma, is a rare type of cancer. LEC can affect any organ, but it is most common in the head and neck region. Sinonasal lymphoepithelial carcinoma (SNLEC) is an example of LEC that can occur in our body and it is very rare. LEC has usually associated with Epstein-Barr virus (EBV) infection and gives a picture of undifferentiated carcinoma with an intermixed reactive lymphoplasmacytic infiltrate on histology. It is pretty difficult to commit to a diagnosis, therefore histological examination and immunohistochemical investigations are used to determine the ultimate definite diagnosis. Most cases present with locally aggressive illness, which may or may not include regional lymph node metastases. General treatment depends on the patient’s condition, including surgical resection, radiation therapy, and chemotherapy. Herein, we present a case of a young, previously healthy gentleman with sudden onset of anosmia with left eye blurred vision whose final diagnosis was EBV negative SNLEC subsequently managed by radiotherapy. International Journal of Human and Health Sciences Vol. 07 No. 01 Jan’22 Page: 89-94